THE FACTOR RELATED TO SUCCESSFULLY ENHANCING RESEARCH COMPETENCE AMONG NURSING INSTRUCTORS FOR IMPROVING EDUCATIONAL QUALITY ASSURANCE OF NURSING EDUCATIONAL INSTITUTIONS - Hengyotmark, Arunee; Meecharn, Surachai; Suwathanpornkul, Ittipaat (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
The purposes of this study were to explore factors related to successfully enhancing research competency among nursing instructors for improving educational quality assurance of nursing educational institutions and to understand the barriers of research practices. A qualitative research methodology was based on a case study approach. The key informants consisted of 9 research experts in nursing education selected by purposive selection from 7 institutions in Bangkok Metropolitan. The data were collected by observation and in-depth interview and examined the content validity by experts. Content analysis was used in this study. The results revealed that four major themes were related to 1) advisor or mentor 2) time management 3) knowledge and skills in research practice and 4) research network building. Meanwhile, the barriers to research practice included job burnout, a lack of motivation, a long waiting time for approval from the institutional review board (IRB), a lack of management support, an unfavorable climate, and no searching skills. These should be considered by administrators and relevant personnel at all levels and nursing instructors for improvement of competence, educational quality, society, and eventually the nation.